Colorization of Grayscale Images Using KPE and LBG Vector Quantization Techniques - Bhandari, Nikita; Kaur, Gagandeep (International Journal of Computer Sciences and Engineering, 2025)
Colorization is a practice of adding colors to gray scale images and videos. This research aims at replacing each pixel value of grayscale image by the required color pixel value. Adding colors to grayscale images makes them more attractive and observable. It is easy for human visual system to recognize color information more proficiently as compared to gray information. Automation of this process is very important as manual colorization takes a lot of time and effort. In the proposed method, Kekre’s Proportionate Error (KPE) codebook is used and five different vector quantization (VQ) codebook sized alias 32, 64, 128, 256 and 512 are considered. By using eight different color models: RGB, Kekre’s LUV, YCbCr, YUV, YIQ, and Kekre’s Biorthogonal color models and five VQ codebooks, total 40 versions of proposed colorization method are found. Testing is done on 30 images of different classes and results are compared with the existing method of LBG based image coloring. It is observed that the use of higher codebook sizes and YCbCr color model enhances the colorization.